Coastal Waters Monitoring Using Remote Sensing Technology - Vignudelli, Stefano; Benveniste, Jérôme (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Around 10% of the global population lives in the world's coastal zones, mostly concentrated in the world's largest megacities. In many regions, the population is exposed to a variety of natural hazards and space-based observations. This Special Issue will focus on the usage of remote sensing alone or in synergy with in situ measurments and modeling tools to provide precise and systematic information about processes acting in the world's coastal zones.